Development of E-Module Teaching Materials Gymnastics Learning Theory and Practice Course - Oktariyana, Oktariyana; Sukmawati, Noviria; Norito, Tri Bayu Norito Bayu; Nita, Perabu; Pebriantika, Leni (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2025)
Objective. This study focuses on the development and evaluation of e-module teaching materials designed for both the theoretical and practical aspects of gymnastics learning. Materials and Methods. The approach employed is a systematic development process consisting of 10 distinct stages, aligned with the developmental framework established by Borg and Gall. In this study, the process is structured into four distinct stages: (1) gathering research and information, (2) planning, (3) creating a preliminary version of the product, and (4) conducting preliminary field testing. Result. The findings from the media expert validation assessment indicate an average percentage result of 82.6%, categorized as valid and usable with revisions. In contrast, the material expert validation assessment yielded an average percentage result of 86.5%, classified as very valid and usable. Additionally, the learning expert validation assessment achieved an average percentage result of 81%, also categorized as valid and usable with revisions. Furthermore, the outcomes of the small-scale test indicate a result of 77%, categorized as